The investigation of the Effect of using E-learning in Database Course by using Moodle (Comprehensive Journal of Science, 2026)
Despite the proliferation of E-learning in education world-wide, this methodology is not implemented on Libyan context. therefore, there is a need to investigate the effect of deploying eLearning methodology in higher education. The aim purpose of this study is to develop E-learning database by using Moodle open source (learning management system). The secondary purpose is to compare the effects of two different modes of teaching   (E-learning, and traditional classroom) on student achievement used in database course at (High institute of medical technology Abosalim ). A study was developed to examine student’s achievement in database course by comparing results of final test for both modes of delivery. The sample was (16 students at classroom mode and 15 students at E-learning mode).The final results showed that the mean difference between the test of the two groups by using the T.test was that the E-learning group obtained a higher achievement of statistical significance than the traditional education group at the significance level (P
Keywords: E-learning; Database; Teaching; Moodle